The Interplay of Stability between Donor and Acceptor Materials in a Fullerene‐Free Bulk Heterojunction Solar Cell Blend. Issue 46 (28th October 2020) - Sudakov, Ivan; Van Landeghem, Melissa; Lenaerts, Ruben; Maes, Wouter; Van Doorslaer, Sabine; Goovaerts, Etienne
Abstract: With rapid advances in material synthesis and device performance, the long‐term stability of organic solar cells has become the main remaining challenge toward commercialization. An investigation of photodegradation in blend films of the donor polymer poly(3‐hexylthiophene) (P3HT) and the rhodanine‐flanked small molecule acceptor 5, 5′‐[(9, 9‐dioctyl‐9 H ‐fluorene‐2, 7‐diyl)bis(2, 1, 3‐benzothiadiazole‐7, 4‐diylmethylidyne)]bis[3‐ethyl‐2‐thioxo‐4‐thiazolidinone] (FBR) is presented in an ambient atmosphere. The photobleaching kinetics of the pure materials and their blends is correlated with the generation of radicals and triplet excitons using optical and magnetic resonance techniques. In addition, spin‐trapping methods are employed to identify reactive oxygen species (ROS). In films of P3HT, FBR, and the P3HT:FBR blend, superoxide is generated by electron transfer to molecular oxygen. However, it is found that the generation of singlet oxygen by energy transfer from the FBR triplet state is responsible for the poor stability of FBR and for the accelerated photodegradation at later times of the P3HT:FBR blend. In the early stage of degradation of the neat blend, it is protected from singlet oxygen by the fast donor–acceptor charge transfer, which competes with triplet exciton formation. These results provide initial input for a rational design of donor and acceptor materials through tuning the molecular singlet and triplet energy levels to prevent ROS‐related photodegradation. Abstract : Nonfullerene acceptors offer new opportunities for high efficiencies in organic solar cells, but the suppression of photodegradation of the materials in the presence of dioxygen is essential. The complex behavior of the reactive oxygen species superoxide and singlet oxygen in the degradation of the donor polymer poly(3‐hexylthiophene), the small molecule acceptor 5, 5′‐[(9, 9‐dioctyl‐9H‐fluorene‐2, 7‐diyl)bis(2, 1, 3‐benzothiadiazole‐7, 4‐diylmethylidyne)]bis[3‐ethyl‐2‐thioxo‐4‐thiazolidinone], and their blends is unraveled in detail.